A strain of cucumber mosaic cucumovirus causing mosaic in marigold in India - and I.D. GARG*, DOOMAR SINGH, Q.A. NAQVI (Indian Phytopathology, 2002)
A strain of cucumber mosaic virus causing marigold mosaic was partially characterized. The virus was isolated from diseased marigold (Tagetes erecta) plant growing at and around Aligarh, India. Diseased plants showed mosaic, mottling and stunting. Infected leaf tissue showed the presence of isometric virus particles measuring about 29 nm in diameter, resembling those of cucumoviruses when viewed using an electron microscope. There was enhanced trapping and decoration of virions with antisera to strains of cucumber mosaic virus, namely, soybean stunt (CMV-SS) and pea strain (CMV-P) in immunoelectron microscopic studies. There was neither enhancement of trapping nor any perceptible decoration of virions with antiserum to CMV-K8 cucumovirus. Host range, biophysical properties and non-persistent transmission through Aphis gossypii, A. craccivora and Myzus persicae also supported the diagnosis of the virus as a strain of cucumber mosaic virus.